Budidaya Tanaman TOGA: Solusi Pekarangan Produktif dan Ramah Lingkungan - Ilham Fahri; Siti Riqsya Aulia Ramadona; Lindawati Lindawati; Yunizir Djakfar; Rini Efrianti (Institut Teknologi dan Bisnis Semarang, 2025)
This community service project aims to develop the cultivation of medicinal plants (TOGA) in Persiapan Sinar Bhakti Village, OKU Regency, as a solution for creating productive and environmentally friendly yards that support food security and public health. The method used in this activity involves providing training to the local community on how to cultivate TOGA plants, followed by the planting of various medicinal plants and vegetables in the available yard. The land used measures 10x15 meters and is divided into two plant blocks, namely Toga Tulip and Toga Wijaya. Some of the plants cultivated include Turmeric, Lemongrass, Kencur, Kumis Kucing, Galangal, White Turmeric, Saga Leaves, Black Sugarcane, Mahkota Dewa, Temulawak, Ginger, as well as vegetables such as Chili, Eggplant, and Water Spinach. This activity not only has a positive impact on the sustainability of yard utilization but also enhances the community's knowledge on the use of medicinal plants for health purposes, while providing an alternative source of income through the cultivation of marketable vegetables. The results of this activity show that the community of Sinar Bhakti Village has successfully understood and implemented the techniques for cultivating medicinal plants and vegetables. This success is expected to improve food security, promote healthier lifestyles, and reduce reliance on chemical medicines for treatment.